Peace and democratic society - Sen, Amartya, 1933-; Commonwealth Commission on Respect and Understanding; Commonwealth Secretariat; Open Book Publishers (Open Book Publishers, 2011)
"Recent acts of terrorism and the current unrest in the Middle East remind us how important it is to understand the relationship between peace and democracy. In an insightful introductory essay to this report, Nobel laureate Amartya Sen challenges widely accepted explanations for violence. He makes a plea for a global, multilateral debate on the causes of conflict, and an understanding of the multiple identities of the individuals involved. The introductory essay draws on the findings of the Commonwealth Commission on Respect and Understanding, which was chaired by Sen, and established to promote mutual communication and understanding among all faiths and communities in the Commonwealth. Its timely report, "Civil Paths to Peace", suggests that governments, media and educators-indeed, everyone-must take the time to understand the complexities around violent behaviour and its causes, without prejudging what these might be."--Publisher's website.
Part I. Violence and civil society / by Amartya Sen -- Part II. Civil paths to peace: Report of the Commonwealth Commission on Respect and Understanding -- Members of the Commission -- Executive Summary -- 1. Why do Respect and Understanding Matter? -- 2. The Nature and Nurture of Violence -- 3. Poverty, Inequality and Humiliation -- 4. History, Grievance and Conflict -- 5. Political Participation -- 6. The Role of Media and Communication -- 7. Young People and Education -- 8. Multilateralism and the International Order -- 9. The Way Forward and Conclusions -- Afterward: Original preface and letter of presentation to the Report - References -- Bibliography -- Appendix: Written submissions to the Commonwealth Commission on Respect and Understanding -- Index.
At foot of title: Commonwealth Secretariat.
Available through Open Book Publishers.
Includes bibliographical references (pages 141-142), bibliography (pages 143-146) and index.
Mode of access: World Wide Web.
Description based on print version record.
Keywords: Commonwealth Commission on Respect and Understanding; Conflict management -- International cooperation -- 21st century; Democratization -- 21st century; Nation-building -- International cooperation -- 21st century; Peace -- International cooperation -- 21st century; Security, International -- International cooperation -- 21st century